The effect of supplementing teff (Eragrostis tef) straw with graded levels of cowpea (Vigna unguiculata) and lablab (Lablab purpureus) hays on degradation, rumen particulate passage and intake by crossbred (Friesian X Boran (Zebu)) calves - Ebro, A.; Umunna, N.N.; Nsahlai, I.V.; Osuji, P.O.; Yami, A. (Elsevier, 1995)
This study characterized the degradability of cowpea (Vigna unguiculata) and Dolichos lablab (Lablab purpureus) hays (trial 1) and the effect of these legumes on rumen ammonia concentration (RAC), particulate passage rate (K1) and intake (trial 2) and the degradability of teff (Eragrostis tef) straw (trial 3). Trials 1 and 3 were conducted using ruminally cannulated corssbred (Friesian X Boran) cows. In trial 1, cows were fed native pasture hay ad libitum plus 2.45 kg cottonseed cake head -1 day -1. In trial 2, calves were fed ad libitum teff straw alone or supplemented with three levels (0.5, 1 and 1.5 percent of body weight) of either cowpea or lablab hay. In trial 3, cows were fed teff straw ad libitum supplemented with either cowpea or lablab hay at 1 percent of body weight. Cowpea had similar degradation characteristics to lablab. Supplementation increased RAC (154-218 vs. 48 mg/1; P<0.05) and decreased the mean retention time (MRT; 72.8 vs. 109 h; P<0.01). Total dry matter intake (DMI) increased with increasing level of supplementation. Cowpea and lablab had similar RAC, rate of degradation of teff straw, K1, MRT and DMI. It was concluded that both herbaceous legumes are equally efficient in alleviating nutrient deficiencies incurred when teff straw is fed to calves.